Implementasi Algoritma Mars Pada Penyandian Citra Digital USG - Alfiah Caniago (Bulletin of Information Technology (BIT), 2020)
Digital image is one form of digital data that is currently widely used to store photos, images or works in digital format, one of which is an ultrasound image. In the medical field ultrasound can be used to diagnose several diseases in human organs, one of which is the liver. Digital images are very vulnerable to eavesdropping or data theft by irresponsible parties. In order to maintain the security of ultrasound images can be done by using cryptographic techniques. Cryptographic techniques can encode digital ultrasound images by encrypting them in the form of passwords that are not understood. In this study using the Mars algorithm. To build this computerized application using Visual Basic 2008 as supporting application. This application was created as an effort to minimize the actions of misuse of the ultrasound image.